A new species of Stilipedidae (Amphipoda: Senticaudata) from the South Mid-Atlantic Ridge - Serejo, C. S. (Zootaxa, 2014)
A new species of Alexandrella is herein described based on material from the South Mid-Atlantic Ridge around depths of 4700 m. Samples were collected in the scope of the South MAR ECO (Patterns and Processes of the Ecosystems of the Mid-Atlantic) Project, which was part of the Census of Marine Life (CoML). Until the present study, Alexandrella was restricted to Antarctic and Subantarctic waters, with two species having  extended distributions (Kermadec Trench, Australia and New Zealand). This is the first record of Alexandrella in the deep sea Atlantic, outside the Southern Ocean limits.